An Effective Study on Basic Measures of Indexing in Journals - Barkur, Roshini; Thomas, Jissy (International Journal of Psychosocial Rehabilitation, 2020)
An indexed journal database for any discipline is needed to organize the research articles in a systematic way. It works as a simple bibliometric. An understanding of basic concepts and practices of indexed journal is a must for any author before publishing the article. In this modern era there are various publishers that the authors can approach to publish their articles, thesis, reports, books etc. These publishers have several subject matter experts in various domains who review the submitted articles carefully before publishing the work of the author. Also, indexing reflects the high-quality work of the author which is calculated considering various factors and formulas.